Intrinsic Senses of Early 21st Century Global Internet Discourse - Zernetskaya, Olga; Zernetskiy, Pavel (Respectus Philologicus, 2013)
This article tackles, for the first time, the phenomenon of the intrinsic senses ofglobal internet discourse. The interrelations of artificial and natural languages are analyzed. The notion of the “sewing” senses of the Internet i.e., those containing new, often-used concepts originated from natural languages (English, Russian, Ukrainian, etc.)—is introduced, and their contrastive analysis is carried out. The processes that take place when modifying the senses of already known words and creating new ones show the great influence of modern scientific technologies in general on the global multicultural sense field. All of this is actualized as tackling the issues of producing and translating senses in English internet discourse (English being the main language of the global Internet environment), as solving the problems of their translation with certain modifications into different languages of the world. The article considers various cross-cutting senses, such as web, net, cyber, blogger, etc. It analyzes the history of their appearance ininternet discourse, the expansion of their meanings, and their transformations. It is necessary to emphasize that the terms of internet discourse are inherited from the English language by means of transliteration. In rare cases, such borrowings are semantic calques. When broadcasting internet senses to other subsystems, these senses undergo various semantic processes—evolution, modification, expansion, narrowing, lowering or raising of their statuses (from the established professional terms to slang)—when they enter other, non-Internet discourses, such as social, political, economic, youth.
Keywords: Discourse; Intrinsic Senses of the Internet; Sewing Sense; Interrelations of Artificial and Natural Languages; Contrastive Analysis